Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1182/blood-2019-129872
|View full text |Cite
|
Sign up to set email alerts
|

Increased Early Mortality after Fludarabine and Melphalan Conditioning with Peripheral Blood Grafts in Haploidentical SCT with Post-Transplant Cyclophosphamide

Abstract: The use of post-transplant cyclophosphamide (PTCy) in the context of haploidentical stem cell transplant (haplo-SCT) has led to drastically reduced rates of Graft-vs-Host (GvH) disease through selective depletion of highly allo-reactive donor T-cells. Early trials utilized a reduced-intensity Flu/Cy/TBI preparative regimen and bone marrow grafts; however, relapse rates remained relatively high (Luznik et al. BBMT. 2008). This led to the increased use of myeloablative (MA) regimens for haplo-SCT, which have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Posttransplant cyclophosphamide is associated with some delay in count recovery, which would explain the somewhat paradoxical delay in count recovery and possibly the increased mortality from graft failure and infection observed in the Flu-Mel group . Eastburg et al recently reported that the combination of Flu-Mel with posttransplant cyclophosphamide is poorly tolerated. Others have had difficulty when combining it with busulfan and fludarabine …”
mentioning
confidence: 99%
“…Posttransplant cyclophosphamide is associated with some delay in count recovery, which would explain the somewhat paradoxical delay in count recovery and possibly the increased mortality from graft failure and infection observed in the Flu-Mel group . Eastburg et al recently reported that the combination of Flu-Mel with posttransplant cyclophosphamide is poorly tolerated. Others have had difficulty when combining it with busulfan and fludarabine …”
mentioning
confidence: 99%